Anti-icing film with photo-thermal and ice nucleation capabilities and preparation method thereof
By combining the multi-phase multi-component hybrid materials with photothermal and ice nucleation functions in the anti-ice film, the problem of solid surface icing in low temperature and high humidity environments is solved, and the effect of efficient deicing and reducing the difficulty of deicing is achieved.
Patent Information
- Application Number
- CN202411833233.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
In low temperature and high humidity environments, the solid surface is prone to freezing, which makes it difficult to remove ice and poor effect. The existing passive anti-icing methods are difficult to effectively reduce the adhesion of ice.
Anti-icing films prepared using multi-phase multi-component hybrid materials have a microscopic "sea-island structure" and include polyvinyl matrix, polyelectrolyte composite, aminosilane-modified iron tetraoxide nanoparticles and graphene oxide ice nucleation nanosheets. Through the combined action of photothermal effect and ice nucleation function, efficient deicing is achieved.
By introducing ice nucleation sites locally and reducing the surrounding water vapor pressure, discontinuous ice formation is induced, ice adhesion is reduced, deicing efficiency is improved, and the film surface temperature is increased by photothermal nanoparticles, further reducing the difficulty of deicing.
Smart Images

Figure CN119570097A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-icing coating film having both photothermal and ice nucleation capabilities and a preparation method thereof, belonging to the technical field of anti-icing materials. Background Art
[0002] In low temperature and high humidity environments, solid surfaces are very prone to ice formation, which affects the normal use of power transmission lines, aircraft, wind turbines, and transportation vehicles, and often requires high costs for their operation and maintenance. Therefore, anti-icing / de-icing of solid surfaces has gradually become a research hotspot in related fields.
[0003] In order to solve the problem of ice formation on solid surfaces, active deicing methods such as spraying chemical reagents, heating and melting, and mechanical crushing are currently commonly used, as well as passive anti-icing methods such as coating super-hydrophobic, low ice adhesion and photothermal coatings on the solid surface. The effect and efficiency of these deicing methods directly depend on the state of the ice layer on the solid surface. If the ice layer is continuous, deicing is difficult and the deicing effect is poor; if the ice layer is discrete, the deicing difficulty will be greatly reduced.
[0004] Therefore, there is an urgent need for a deicing film with ice nucleation function that can change the continuous state of the ice layer and reduce the difficulty of deicing. At the same time, combined with the photothermal properties of the deicing film, the purpose of efficient deicing can be achieved. Summary of the invention
[0005] The object of the present invention is to provide an anti-icing film having both photothermal and ice nucleation capabilities and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] According to the present invention, an anti-icing film having both photothermal and ice nucleation capabilities is a multi-phase and multi-component hybrid material having a microscopic "sea-island structure".
[0008] According to the present invention, the anti-icing film comprises four parts: a continuous phase matrix, a polyelectrolyte complex dispersed phase, photothermal nanoparticles and ice nucleation nanosheets.
[0009] According to the present invention, the substrate is a polyethylene film material, and the film thickness is 50 μm to 1000 μm, for example, 50 μm, 100 μm, 200 μm, 500 μm and 1000 μm.
[0010] According to the present invention, the polyelectrolyte complex is a polyacrylic acid-polyethyleneimine complex.
[0011] According to the present invention, the mass ratio of the polyethylene matrix to the polyacrylic acid-polyethyleneimine composite is 1:1 to 20:1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 10:1 and 20:1.
[0012] According to the present invention, the degree of polymerization of the polyacrylic acid is 20 to 10,000, for example, 20, 50, 100, 200, 500, 1,000, 2,000, 5,000 and 10,000.
[0013] According to the present invention, the degree of polymerization of the polyethyleneimine is 3 to 300, for example, 3, 5, 10, 20, 50, 100, 200 and 300.
[0014] According to the present invention, the photothermal nanoparticles are aminosilane-modified ferrosoferric oxide nanoparticles.
[0015] According to the present invention, the mass ratio of the polyethylene matrix to the aminosilane-modified ferrosoferric oxide nanoparticles is 10:1 to 100:1, for example, 10:1, 20:1, 30:1, 40:1, 50:1 and 100:1.
[0016] According to the present invention, the aminosilane-modified ferrosoferric oxide nanoparticles are dispersed in the polyethylene continuous phase and on the polyethylene-polyelectrolyte complex phase interface.
[0017] According to the present invention, the aminosilane is an aminosilane coupling agent known in the art, including but not limited to γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyltriethoxysilane, and γ-aminopropylmethyltrimethoxysilane.
[0018] According to the present invention, the ice nucleation nanosheet is a graphene oxide nanosheet;
[0019] According to the present invention, the graphene oxide nanosheet layer covers the surface of the dispersed phase of the polyacrylic acid-polyethyleneimine composite.
[0020] According to the present invention, the ratio of carbon to oxygen atoms in the graphene oxide nanosheet layer is 2:1 to 3:1, for example, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, or 3.0:1.
[0021] The present invention also provides a method for preparing the above-mentioned anti-icing film, the method comprising the following steps:
[0022] (1) ultrasonically dispersing ferroferric oxide nanoparticles in an organic solvent, adding an aminosilane coupling agent, boiling and refluxing for a period of time, filtering and repeatedly washing the filter cake with ethanol, and vacuum drying to obtain aminosilane-modified ferroferric oxide nanoparticles;
[0023] (2) melt-blending the ferroferric oxide nanoparticles with polystyrene in an internal mixer at high temperature to obtain a polystyrene-based ferroferric oxide nanocomposite material, and then melt-blending the polystyrene-based ferroferric oxide nanocomposite material with polyethylene at high temperature to obtain a polyethylene / polystyrene / ferroferric oxide nanocomposite material;
[0024] (3) hot pressing the polyethylene / polystyrene / ferroferric oxide nanocomposite material at high temperature in a hot pressing molding machine to obtain a polyethylene / polystyrene / ferroferric oxide film;
[0025] (4) immersing the polyethylene / polystyrene / ferroferric oxide film in an organic solvent to dissolve and etch the polystyrene phase, and then washing and drying the polyethylene / ferroferric oxide film repeatedly to obtain the polyethylene / ferroferric oxide film;
[0026] (5) The polyethylene / ferroferric oxide film is repeatedly and alternately immersed in a polyacrylic acid aqueous solution and a polyethyleneimine aqueous solution. After the pits formed by etching the polystyrene phase are filled, it is immersed in a graphene oxide / water dispersion, taken out, repeatedly rinsed with water, and then dried to obtain the final anti-icing film.
[0027] According to the present invention, the organic solvent in step (1) is a solvent known in the art, including but not limited to toluene, xylene, dichloromethane, chloroform, N,N-dimethylformamide, ethanol, tetrahydrofuran, etc.
[0028] According to the present invention, the concentration of ferrosoferric oxide in step (1) is 1 mg / ml to 200.0 mg / ml, for example, 1.0 mg / ml, 2.0 mg / ml, 3.0 mg / ml, 5.0 mg / ml, 10.0 mg / ml, 20 mg / ml, 50 mg / ml, 100 mg / ml and 200 mg / ml;
[0029] According to the present invention, the aminosilane coupling agent in step (1) is an aminosilane coupling agent known in the art, including but not limited to γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyltriethoxysilane, and γ-aminopropylmethyltrimethoxysilane.
[0030] According to the present invention, the mass ratio of the ferrosoferric oxide nanoparticles to the aminosilane coupling agent in step (1) is 10:1 to 1:2.
[0031] According to the present invention, the reaction time in step (1) is 6 h to 24 h, for example, 6 h, 8 h, 10 h, 12 h, 16 h, 20 h and 24 h.
[0032] According to the present invention, the mass ratio of polystyrene to ferrosoferric oxide nanoparticles in step (2) is 5:1 to 50:1.
[0033] According to the present invention, the temperature for melt blending of polystyrene and ferrosoferric oxide in step (2) is 150-220°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C and 220°C.
[0034] According to the present invention, the melt blending time of the polystyrene and ferrosoferric oxide in step (2) is 5 to 30 minutes, for example, 5 minutes, 7 minutes, 9 minutes, 11 minutes, 13 minutes, 15 minutes, 20 minutes, 25 minutes and 30 minutes.
[0035] According to the present invention, the mass ratio of polyethylene to polystyrene / ferrosoferric oxide composite material in step (2) is 1:1 to 20:1.
[0036] According to the present invention, the melt blending temperature of the polyethylene and polystyrene / ferrosoferric oxide composite material in step (2) is 180-220°C, for example, 180°C, 190°C, 200°C, 210°C and 220°C.
[0037] According to the present invention, the melt blending time of the polyethylene and the polystyrene / ferrosoferric oxide composite material in step (2) is 5 to 15 minutes, for example, 5 minutes, 7 minutes, 9 minutes, 11 minutes, 13 minutes and 15 minutes.
[0038] According to the present invention, the hot pressing molding pressure in step (3) is 3 to 15 MPa, for example, 3 MPa, 5 MPa, 7 MPa, 9 MPa, 11 MPa, 13 MPa and 15 MPa.
[0039] According to the present invention, the hot pressing molding temperature in step (3) is 180-220°C, for example, 180°C, 190°C, 200°C, 210°C and 220°C.
[0040] According to the present invention, the hot pressing molding time in step (3) is 1 to 10 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, and 10 minutes.
[0041] According to the present invention, the polyethylene / polystyrene / ferroferric oxide film obtained in step (3) has a thickness of 50 μm to 1000 μm, for example, 50 μm, 100 μm, 200 μm, 500 μm and 1000 μm.
[0042] According to the present invention, the fuel engine solvent in step (4) is a solvent capable of dissolving polystyrene, including but not limited to toluene, xylene, N,N-dimethylformamide, acetone and chloroform.
[0043] According to the present invention, the degree of polymerization of the polyacrylic acid in step (5) is 20 to 10,000, for example, 20, 50, 100, 200, 500, 1,000, 2,000, 5,000 and 10,000.
[0044] According to the present invention, the concentration of the polyacrylic acid aqueous solution in step (5) is 1% to 50%, for example, 1%, 2%, 5%, 10%, 20% and 50%.
[0045] According to the present invention, the degree of polymerization of the polyethyleneimine in step (5) is 3 to 300, for example, 3, 5, 10, 20, 50, 100, 200 and 300.
[0046] According to the present invention, the concentration of the polyethyleneimine aqueous solution in step (5) is 1% to 50%, for example, 1%, 2%, 5%, 10%, 20% and 50%.
[0047] According to the present invention, the carbon-oxygen atom ratio of the graphene oxide nanosheet layer in step (5) is 2:1 to 3:1, for example, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1.
[0048] According to the present invention, the graphene oxide concentration in the graphene oxide dispersion in step (5) is 0.1 to 10 mg / ml, for example, 0.1 mg / ml, 0.2 mg / ml, 0.5 mg / ml, 1.0 mg / ml, 2.0 mg / ml, 5.0 mg / ml and 10.0 mg / ml.
[0049] The technical effects and advantages of the present invention are as follows:
[0050] The present invention introduces graphene oxide ice nucleation sites in local areas of the film surface to promote water vapor to freeze on the graphene oxide surface, and inhibits ice transfer by reducing the water vapor pressure in the surrounding area, preventing the occurrence of ice on the polyethylene surface, inducing the formation of a discontinuous ice layer, which can greatly reduce the adhesion of the ice layer on the film surface and make it easier to remove. At the same time, the introduction of ferroferric oxide photothermal nanoparticles in the polyethylene phase and phase interface can increase the surface temperature of the film under light, further reducing the difficulty of deicing, and making the film show a more excellent deicing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 .Ice nucleation temperature of the samples obtained in Examples (1), (2), (3), (4) and (5) of the present invention at a cooling rate of 5°C / min.
[0052] Figure 2.Temperature rise curves of the samples obtained in Examples (1), (2), (3), (4) and (5) of the present invention under 1 sun illumination intensity.
[0053] Figure 3 Ice adhesion strength of the samples obtained in Examples (1), (2), (3), (4) and (5) of the present invention at -40°C. DETAILED DESCRIPTION
[0054] The present invention will be further described below in conjunction with the embodiments. It should be noted that the following embodiments cannot be used as a limitation of the protection scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0055] Embodiment 1:
[0056] (1) 10.0 g of ferroferric oxide nanoparticles were ultrasonically dispersed in 200 ml of toluene, 5.0 g of γ-aminopropyltriethoxysilane was added, and the mixture was subjected to boiling reflux reaction for 12 h. After filtering, the filter cake was repeatedly washed with ethanol, and then vacuum dried to obtain aminosilane-modified ferroferric oxide nanoparticles;
[0057] (2) melt blending 4.0 g of ferroferric oxide nanoparticles and 40.0 g of polystyrene in an internal mixer at 190° C. for 10 min to obtain a polystyrene / ferroferric oxide nanocomposite; then melt blending 10.0 g of the polystyrene / ferroferric oxide nanocomposite with 30.0 g of polyethylene at 200° C. for 7 min to obtain a polyethylene / polystyrene / ferroferric oxide nanocomposite;
[0058] (3) hot pressing the polyethylene / polystyrene / ferroferric oxide nanocomposite material in a hot pressing molding machine at 200° C. and 10 MPa for 3 min to obtain a polyethylene / polystyrene / ferroferric oxide film with a thickness of 100 μm;
[0059] (4) immersing the polyethylene / polystyrene / ferroferric oxide film in toluene to dissolve and etch the polystyrene phase, repeatedly washing with toluene and drying to obtain the polyethylene / ferroferric oxide film;
[0060] (5) The polyethylene / ferroferric oxide film is repeatedly and alternately immersed in a 10% aqueous solution of polyacrylic acid (degree of polymerization 100) and a 10% aqueous solution of polyethyleneimine (degree of polymerization 20). After the pits formed by etching the polystyrene phase are filled, it is immersed in a 1.0 mg / ml graphene oxide (carbon-oxygen ratio of 2.2) / water dispersion. The film is taken out, rinsed repeatedly with water, and then dried to obtain the final anti-icing film.
[0061] Comparative Example 2:
[0062] Compared with Example 1, in step (2), 20.0 g of polystyrene / ferroferric oxide nanocomposite material and 20.0 g of polyethylene were melt-blended.
[0063] Comparative Example 3:
[0064] Compared with Example 1, the ratio of carbon to oxygen atoms in graphene oxide is 2.7.
[0065] Comparative Example 4:
[0066] Compared with Example 1, the subsequent steps (4) and (5) are not performed, and the polyethylene / polystyrene / ferroferric oxide film is the final product.
[0067] Embodiment 5:
[0068] (1) 10.0 g of ferroferric oxide nanoparticles were ultrasonically dispersed in 200 ml of dichloromethane, 10.0 g of γ-aminopropyltriethoxysilane was added, and the mixture was subjected to boiling reflux reaction for 24 h. After filtering, the filter cake was repeatedly washed with ethanol, and then vacuum dried to obtain aminosilane-modified ferroferric oxide nanoparticles;
[0069] (2) 8.0 g of ferroferric oxide nanoparticles and 40.0 g of polystyrene were melt blended in an internal mixer at 200° C. to obtain a polystyrene / ferroferric oxide nanocomposite material after 12 min; then 20.0 g of the polystyrene / ferroferric oxide nanocomposite material was melt blended with 20.0 g of polyethylene at 220° C. for 10 min to obtain a polyethylene / polystyrene / ferroferric oxide nanocomposite material;
[0070] (3) hot pressing the polyethylene / polystyrene / ferroferric oxide nanocomposite material in a hot pressing molding machine at 220° C. and 15 MPa for 5 min to obtain a polyethylene / polystyrene / ferroferric oxide film with a thickness of 150 μm;
[0071] (4) immersing the polyethylene / polystyrene / ferroferric oxide film in N,N-dimethylformamide to dissolve and etch the polystyrene phase, repeatedly washing with acetone and drying to obtain the polyethylene / ferroferric oxide film;
[0072] (5) The polyethylene / ferroferric oxide film is repeatedly and alternately immersed in a 10% aqueous solution of polyacrylic acid (degree of polymerization 60) and a 10% aqueous solution of polyethyleneimine (degree of polymerization 30). After the pits formed by etching the polystyrene phase are filled, it is immersed in a 0.5 mg / ml graphene oxide (carbon-oxygen ratio of 2.2) / water dispersion. The film is taken out, rinsed repeatedly with water, and then dried to obtain the final anti-icing film.
Claims
1. An anti-icing film with both photothermal and ice nucleation capabilities, characterized in that: The anti-icing film is a multi-phase and multi-component hybrid material, which includes four parts: a continuous phase matrix, a polyelectrolyte complex dispersed phase, photothermal nanoparticles and ice nucleation nanosheets, and has a microscopic "sea-island structure".
2. The anti-icing film according to claim 1, characterized in that The continuous phase is a polyethylene film material, the dispersed phase polyelectrolyte complex is a polyacrylic acid-polyethyleneimine complex, and the mass ratio of the polyethylene matrix to the polyacrylic acid-polyethyleneimine complex is 1:1-20:
1.
3. The anti-icing film according to claim 1, characterized in that: The photothermal nanoparticles are aminosilane-modified ferroferric oxide nanoparticles, and the mass ratio of the aminosilane-modified ferroferric oxide nanoparticles to the polyethylene matrix is 1:100 to 1:
10.
4. The anti-icing film according to claim 1, characterized in that: The ice nucleation nanosheet is a graphene oxide nanosheet layer, and the ratio of carbon to oxygen atoms in the graphene oxide nanosheet layer is 2:1 to 3:
1.
5. A method for preparing an anti-icing film having both photothermal and ice nucleation capabilities, characterized in that: The following steps are involved: (1) ultrasonically dispersing ferroferric oxide nanoparticles in an organic solvent, adding an aminosilane coupling agent, boiling and refluxing for a period of time, filtering and repeatedly washing the filter cake with ethanol, and vacuum drying to obtain aminosilane-modified ferroferric oxide nanoparticles; (2) melt-blending the ferroferric oxide nanoparticles with polystyrene in an internal mixer at high temperature to obtain a polystyrene / ferroferric oxide nanocomposite material, and then melt-blending the nanoparticles with polyethylene at high temperature to obtain a polyethylene / polystyrene / ferroferric oxide nanocomposite material; (3) hot pressing the polyethylene / polystyrene / ferroferric oxide nanocomposite material at high temperature in a hot pressing molding machine to obtain a polyethylene / polystyrene / ferroferric oxide film; (4) immersing the polyethylene / polystyrene / ferroferric oxide film in an organic solvent to dissolve and etch the polystyrene phase, and then washing and drying the polyethylene / ferroferric oxide film repeatedly to obtain the polyethylene / ferroferric oxide film; (5) The polyethylene / ferroferric oxide film is repeatedly and alternately immersed in a polyacrylic acid aqueous solution and a polyethyleneimine aqueous solution. After the pits formed by etching the polystyrene phase are filled, it is immersed in an oxide graphite foot aqueous dispersion, taken out, repeatedly rinsed with water, and then dried to obtain the final anti-icing film.
6. The preparation method according to claim 5, characterized in that: The concentration of ferrosoferric oxide in step (1) is 1 mg / ml to 200.0 mg / ml, the mass ratio of ferrosoferric oxide nanoparticles to aminosilane coupling agent is 10:1 to 1:2, and the reaction time is 6 h to 24 h.
7. The preparation method according to claim 5, characterized in that: The mass ratio of polystyrene to ferroferric oxide nanoparticles in step (2) is 5:1 to 50:1, the temperature of melt blending of polystyrene and ferroferric oxide is 150 to 220° C., and the melt blending time is 5 to 30 min.
8. The preparation method according to claim 5, characterized in that: The mass ratio of polyethylene to polystyrene / ferroferric oxide composite material in step (2) is 1:1-20:1, the melt blending temperature of polyethylene to polystyrene / ferroferric oxide composite material is 180-220°C, and the melt blending time is 5-15min.
9. The preparation method according to claim 5, characterized in that: The hot pressing molding pressure in step (3) is 3-15 MPa, the hot pressing molding temperature is 180-220° C., the molding time is 1-10 min, and the thickness of the obtained polyethylene / polystyrene / ferroferric oxide film is 50 μm-1000 μm.
10. The preparation method according to claim 5, characterized in that: The concentration of the polyacrylic acid aqueous solution in step (5) is 1% to 50%, the concentration of the polyethyleneimine aqueous solution is 1% to 50%, the concentration of graphene oxide in the graphene oxide dispersion is 0.1 to 10 mg / ml, and the ratio of carbon to oxygen atoms in the graphene oxide nanosheet is 2:1 to 3:1.
Citation Information
Cited By
Preparation method and application of composite micro-groove super-hydrophobic low-ice-adhesion photo-thermal film
CN120737420A